2016
DOI: 10.1242/dmm.022939
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic roles for phosphomannomutase type 2 in a new Drosophila congenital disorder of glycosylation disease model

Abstract: Congenital disorders of glycosylation (CDGs) constitute a rapidly growing family of human diseases resulting from heritable mutations in genes driving the production and modification of glycoproteins. The resulting symptomatic hypoglycosylation causes multisystemic defects that include severe neurological impairments, revealing a particularly critical requirement for tightly regulated glycosylation in the nervous system. The most common CDG, CDG-Ia (PMM2-CDG), arises from phosphomannomutase type 2 (PMM2) mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 88 publications
(160 reference statements)
2
34
0
Order By: Relevance
“…Interestingly, neuronal FMRP regulates synaptic matrix metalloproteinase (MMP) classes in Drosophila , which sculpt intercellular signaling via proteolytic cleavage of extracellular proteins [63,64,65]. In the Drosophila FXS model, MMP levels are elevated, resulting in altered intercellular signaling, including trans -synaptic Wnt signaling [66,67]. This mechanism depends on regulation of the cell surface Wnt co-receptor Heparan Sulfate Proteoglycan (HSPG) Dally-like Protein (Dlp).…”
Section: Part Iii: New Progress In Activity-dependent Synapse Developmentioning
confidence: 99%
“…Interestingly, neuronal FMRP regulates synaptic matrix metalloproteinase (MMP) classes in Drosophila , which sculpt intercellular signaling via proteolytic cleavage of extracellular proteins [63,64,65]. In the Drosophila FXS model, MMP levels are elevated, resulting in altered intercellular signaling, including trans -synaptic Wnt signaling [66,67]. This mechanism depends on regulation of the cell surface Wnt co-receptor Heparan Sulfate Proteoglycan (HSPG) Dally-like Protein (Dlp).…”
Section: Part Iii: New Progress In Activity-dependent Synapse Developmentioning
confidence: 99%
“…Intercellular trans-synaptic signaling acts as a core modulator of NMJ structure, function and motor output, including regulation of bouton number, synaptic vesicle cycling and coordinated muscle motor function (JumboLucioni et al, 2016;Parkinson et al, 2016;Wu et al, 2010). Furthermore, our recent studies have revealed highly aberrant transsynaptic signaling in mmp1 and mmp2 mutants , and within the Mmp-dependent FXS disease model (Friedman et al, 2013).…”
Section: Timp Facilitates Coordinated Muscle Peristalsis During Locommentioning
confidence: 96%
“…Mutant animals or tissue-specific mosaics can be produced by simply crossing sgRNA-expressing flies to germline-specific Cas9 or somatic tissuespecific GAL4>Cas9 flies, respectively (Kondo and Ueda 2013;Port et al 2014;Port and Bullock 2016). A number of recent studies in Drosophila have used transgenic CRISPR for LOF, for example to identify novel modifiers of tauopathies (Butzlaff et al 2015;Dourlen et al 2017) or Parkinson's disease (Chen et al 2017;Rousseaux et al 2018); to model congenital disorders of glycosylation (Parkinson et al 2016); to identify genes that regulate tumorigenesis (Das et al 2013;Mishra-Gorur et al 2019); and to study inflammation and immunity (Lee et al 2018;Liu et al 2018).…”
Section: Trip-crispr Knockout (Trip-ko)mentioning
confidence: 99%